Konsep Pemanfaatan Bangunan Cagar Budaya Di Kawasan Kota Lama Semarang - Ardiana Yuli Puspitasari; Eppy Yuliani (Jurnal Planologi, 2019)
ABSTRACTThe Old City area of Semarang is one of the areas designated as part of the heritage city of Semarang. Historically and the position of this region is very important role for the development of the city of Semarang and has important value for the science of urban planning, where the history of the formation of the city of Semarang and its development can not be separated from the existence of the Old City Area Semarang. Along with the development of the increasingly widespread city of Semarang, the old city of Semarang has long been abandoned and experienced environmental degradation. This of course has an effect on the area that is getting increasingly slum and left unchecked, whereas on the other hand the old city area has important values that must be maintained and maintained. The omission of important buildings that have historical value also continues to occur and causes the area to be slum and unhealthy. Through this research, there are goals to be achieved, namely important buildings identified as cultural heritage buildings are utilized by various conservation measures, so that the buildings can be functioned through adaptation of more present and complementary functions so that the old city area becomes alive and more productive. The method used to achieve these objectives is descriptive empirical which begins with extracting strategic issues in the field through interviews with building owners, the surrounding community and the Semarang City Government (Bappeda), as well as the old city area management body (BPK2L). The results of this study are that the concept of building utilizatio /function is carried out on buildings that are included in the first priority of handling, which are then categorized into 8 (eight) in accordance with the conditions and problems that occur in cultural heritage buildings. The concept of using cultural heritage buildings is directed as: museums, offices, art galleries, cafes/restaurants, souvenir shops, meeting rooms, homestays / guest houses, and places to sell antiques.Keywords: concepts, utilization, buildings, cultural heritage  ABSTRAKKawasan Kota Lama Semarang merupakan salah satu kawasan yang ditetapkan sebagai bagian dari kota pusaka Semarang. Secara historis dan posisi kawasan ini sangat penting perannya terhadap perkembangan Kota Semarang dan memiliki nilai penting bagi ilmu perencanaan wilayah kota, dimana sejarah terbentuknya Kota Semarang dan perkembangannya tidak terlepas dari keberadaan Kawasan Kota Lama Semarang. Seiring dengan perkembangan Kota Semarang yang semakin meluas, maka telah lama kawasan kota lama Semarang ditinggalkan dan mengalami degradasi lingkungan. Hal ini tentu saja berpengaruh terhadap kawasan yang semakin lama semakin kumuh dan dibiarkan, padahal disisi lain kawasan kota lama memiliki nilai penting yang harus dipertahankan dan terus dijaga. Pembiaran terhadap bangunan-bangunan penting yang memiliki nilai sejarah juga terus terjadi dan menyebabkan kawasan menjadi kumuh dan tidak sehat. Melalui penelitian ini, maka ada tujuan yang ingin dicapai yaitu bangunan-bangunan penting yang teridentifikasi sebagai bangunan cagar budaya termanfaatkan dengan berbagai tindakan pelestarian, sehingga bangunan-bangunan tersebut dapat difungsikan melalui adaptasi fungsi yang lebih kekinian dan saling mengisi sehingga kawasan kota lama menjadi hidup dan semakin produktif. Metode yang digunakan untuk mencapai tujuan tersebut adalah deskriptif empirik yang diawali dengan penggalian isu-isu strategis di lapangan melalui wawancara dengan pemilik bangunan, masyarakat sekitar dan Pemerintah Kota Semarang (Bappeda), serta badan pengelola kawasan kota lama (BPK2L). Hasil dari penelitian ini adalah konsep pemanfaatan/fungsi bangunan dilakukan pada bangunan yang masuk dalam prioritas I penanganan yang kemudian dikategorikan menjadi 8 (delapan) sesuai dengan kondisi dan permasalahan yang terjadi pada bangunan cagar budaya. Konsep pemanfataan bangunan cagar budaya diarahkan sebagai: museum, kantor, galeri seni, cafe/restoran, souvenir shop, meeting room, homestay/guest house, dan tempat penjualan barang antik. Kata kunci: konsep, pemanfataan, bangunan, cagar budaya